Isolation of lactic acid bacteria from cocoa bean fermentation as potential antibacterial agent against ESKAPE pathogens - Noraziah Mohamad Zin,; Auni Nadzirah Abd Rashid,; Nur Asyikin Zulkhairi,; Nur Aqilah Ridzman,; Khairul Bariah Sulaiman,; Nur Faizah Abu Bakar,; Asif Sukri, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study aimed to evaluate the antibacterial activity of microorganisms isolated before and during cocoa fermentation against ESKAPE pathogens. Microorganisms from cocoa fermentation process were isolated on the selective media and were tested against ESKAPE pathogens. Total titratable acidity, minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) of cell-free supernatant from lactic acid bacteria (LAB) were determined. The presence of bacteriocin and antibacterial activity were determined. LAB was identified through molecular and biochemical tests. Ninety-five and 134 isolates were obtained from the fermentation of Sungai Balung 25 (BR25) clone and mixed clones, respectively. Screening of antibacterial activity showed that 26 isolates of LAB from the cocoa fermentation process had antibacterial activity against ESKAPE pathogens (zone of inhibition ≥11 mm). Cell-free supernatant from some LAB demonstrated potent antibacterial activity against some ESKAPE pathogens through MIC and MBC and evaluation. Furthermore, one isolate (mix48M01) exhibited antibacterial activity against Klebsiella pneumoniae, Pseudomonas aeruginosa, Enterobacter spp., methicillin-resistant Staphylococcus aureus, and Enterococcus raffinousus. An increase in the diameter of inhibition zone was observed as the lactic acid production increased. Gram-positive bacteria isolates were more resistant to LAB than Gram-negative bacteria. Bacteriocin with good antibacterial activity was also detected from the LAB examined. Molecular analysis showed that 13 LAB shared >99% sequence similarity to Lactobacillus fermentum CECT 562 while one isolate shared sequence similarity <98%, indicating that it might be a novel Lactobacillus species. Isolated LAB from this study exhibited high antibacterial activity against ESKAPE pathogens and could be investigated further as potential probiotics and antibacterial agents in the future.